The Influence of Transformational Leadership Principal on Teacher Performance Elementary School - Elis Suryati; Lutfi Nur; Risbon Sianturi (Universitas Pendidikan Indonesia (UPI), 2023)
The principal is a figure who has an important role in creating a conducive working climate in schools. The principal's transformational leadership style can affect teacher motivation, commitment, and performance. This study aims to determine the effect of transformational leadership and organizational culture on teacher performance. This study used explanatory research with a sample of 64 teachers taken from teachers elementary school in the Cibalong Cluster 2 area. The research instrument used regarding transformational leadership is the MLQ (Multifactor Leadership Questionnaire) questionnaire which consists of four indicators, namely Idealized Influence, Inspirational Motivation, Intellectual Stimulation, and Individualized Consederation. Meanwhile, to measure teacher performance is in the form of a questionnaire that contains pedagogic, personality, social, and professional aspects. The results of the analysis show that there is a significant influence of transformational leadership on teacher performance (sig.=0.0000.05); Constant value of 16.409 which means that if there is no transformational leadership then the teacher's performance value is 16.409; The value of the transformational leadership regression coefficient is 0.701 which indicates that 1% of transformational leadership, the teacher's performance will increase by 0.724; and the R Square value of 0.614 which indicates that the effect of transformational leadership on teacher performance is 61.4%. These results can be concluded that transformational leadership and organizational culture influence teacher performance with an influence of 64%. This result is due to the leadership style that encourages teachers to develop and deepen the existing understanding of teacher competencies namely pedagogic, personality, social and professional. The effectiveness of transformational leadership engagement will also improve teacher performance.